Smaug assembles an ATP-dependent stable complex repressing nanos mRNA translation at multiple levels - Jeske, Mandy (Nature Publishing Group, 2011)
The nanos (nos) mRNA encodes the posterior determinant of the Drosophila embryo. Translation of the RNA is repressed throughout most of the embryo by the protein Smaug binding to Smaug recognition elements (SREs) in the 3′ UTR. Translation is locally activated at the posterior pole by Oskar. This paper reports that the SREs govern the time- and ATP-dependent assembly of an exceedingly stable repressed ribonucleoprotein particle (RNP) in embryo extract. Repression can be virtually complete. Smaug and its co-repressor Cup as well as Trailer hitch and the DEAD box protein Me31B are part of the repressed RNP. The initiation factor eIF4G is specifically displaced, and 48S pre-initiation complex formation is inhibited. However, later steps in translation initiation are also sensitive to SRE-dependent inhibition. These data confirm several previously untested predictions of a current model for Cup-dependent repression but also suggest that the Cup model by itself is insufficient to explain translational repression of the nos RNA. In the embryo extract, recombinant Oskar relieves translational repression and deadenylation by preventing Smaug's binding to the SREs.